Implementation of Lying Turning During Phototherapy to Reduce Bilirubin Levels in Hyperbilirubinemia Babies - Anisa Oktiawati; Meilina Tri Wahyuni (Rajaki of Tulip Medika Publisher, 2024)
Neonatal jaundice is a condition that often occurs in newborn babies. Hyperbilirubin occurs due to high levels of bilirubin in the blood which is marked yellow on the sclera and skin. Bilirubin levels that are too high can cause kernicterus if not treated immediately. To reduce bilirubin levels, phototherapy is indicated. The benefit of applying bed transfer therapy is as a way to reduce bilirubin levels evenly in neonates when phototherapy is carried out. According to the United Nations Children's Fund (UNICEF), there are 1.8% of infant deaths caused by hyperbilirubin from all perinatal cases that occur in the world. The incidence of infant hyperbilirubinemia in Indonesia is around 50% of term babies whose skin, mucosa and facial changes become yellowish (jaundice). In preterm babies the incidence reaches 75%. Implement bed shifting during phototherapy to determine the effectiveness of reducing bilirubin levels in hyperbilirubinemia patients. This research is an analytical descriptive research with a case study approach. The subjects of this study were 2 hyperbilirubin patients aged 18 days and 6 days. his research was conducted in June 2024 at the Hospital. Data was obtained through interviews, observation, physical examination and laboratory results of bilirubin levels. Data is presented in the form of narrative text and research instrument sheet tables. This research has gone through an ethical feasibility test. The results of the case study research using bed shifting during phototherapy resulted in a reduction in bilirubin levels in both subjects. The results of the decrease in the first patient were total bilirubin 13.36 mg/dl, direct bilirubin 0.69 mgdl, indirect bilirubin 12.67 mg/dl, the second patient total bilirubin 9.60 mg/dl, direct bilirubin 1.09 mg/dl, Indirect bilirubin 8.51 after being given bed rest during phototherapy for 2 days, the first patient had total bilirubin 10.06 mg/dl, direct bilirubin 0.37 mg/dl, indirect bilirubin 9.67 mg/dl, second patient total bilirubin 8.89 mg/dl, bilirubin direct 0.18 mg/dl, indirect bilirubin 8.71mg/dl. Patients with hyperbilirubinemia are advised to provide adequate breast milk intake and expose themselves to sunlight in the morning between 07.00 – 09.00 for 15 minutes.